“Sometimes We Struggle, Sometimes We Push Back:” The Educational Experiences and Aspirations of Youth with Refugee Backgrounds from the Horn of Africa - Wilson-Forsberg, Stacey; Masakure, Oliver; Kimani-Dupuis, Rosemary; Mondal, Suman (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
This qualitative article focuses on the high school experiences and post-secondary education (PSE) plans of 57 youth with refugee backgrounds from the Horn of Africa living in Ontario. The article is guided by two conceptual frameworks. The first is an anti-oppressive approach, which helps us examine the structural barriers at school that prevent, impede, and discourage the youth from successfully transitioning to PSE. We then use Yosso’s (2005) community cultural wealth framework to highlight the cultural capital that the youth bring from their homes and communities to navigate the challenges at school and embark on a pathway to PSE. Our findings show that while a significant number of the youth continue to face challenges, some are pushing back on the common narrative that Black African refugees are not capable of attending PSE.